A Novel Defined Super-Enhancer Associated Gene Signature to Predict Prognosis in Patients With Diffuse Large B-Cell Lymphoma - Xu, Hong; Li, Yuhang; Jiang, Yanan; Wang, Jinhuan; Sun, Huimeng; Wu, Wenqi; LV, Yangyang; Liu, Su; Zhai, Yixin; Tian, LinYan; Li, Lanfang; Zhao, Zhigang (Frontiers in Genetics, 2022)
Background: Diffuse large B-cell lymphoma (DLBCL) is a genetically heterogeneous disease that can have profound differences in survival outcomes. Despite a variety of powerful prognostic factors and models have been applied, the development of more accurate prognosis and treatment for DLBCL still faces many challenges. The rapid development of research on super-enhancer (SE)-associated genes provides the possibility of its use in prognosis in cancer patients. Here, we aimed to establish a novel effective prognostic model using SE-associated genes from DLBCL. Methods: A total of 1105 DLBCL patients from the Gene Expression Omnibus database were included in this study and were divided into a training set and a validation set. Eleven SE-associated genes (BCL2, SPAG16, PXK, BTG1, LRRC37A2, EXT1, TGFBR2, ANKRD12, MYCBP2, PAX5 and MYC) were initially screened and identified by the least absolute shrinkage and selection operator (Lasso) penalized Cox regression, univariate and multivariate Cox regression analysis.Finally, a risk score model based on these eleven genes was constructed. Results: Kaplan-Meier (K-M) curves showed that the low-risk group appeared to have better clinical survival outcomes. The excellent performance of the model was determined via time-dependent receiver operating characteristic (ROC) curves. A nomogram based on the polygenic risk score was further established to promote reliable prognostic prediction. This study proposed that, the SE-associated-gene risk signature can effectively predict the response to chemotherapy in DLBCL patients. Conclusion: A novel and reliable SE-associated-gene signature that can effectively classify DLBCL patients into high-risk and low-risk groups in terms of overall survival was developed, which may assist clinicians in the treatment of DLBCL.